VITAMIN AND PROVITAMIN PROFILES OF SELECTED VEGETABLES AS AFFECTED BY STORAGE AND DIFFERENT DRYING METHODS - Ogunwole, Olugbenga Adeniran; Mosuro, Aderonke Olufunmilola (Journal of Agricultural Sciences (Belgrade), 2019)
Abstract: Effects of drying methods on vitamin and provitamin composition of selected vegetables during storage was undertaken in this study. Telfaria occidentalis, Celosia argentea (green), Vernonia amygdalina, Moringa oleifera, Launaea taraxacifolia, Curcubita maxima and Celosia argentea (red) were subjected to air drying (AD), oven drying (OD) and freeze drying (FD). The experiment was a 3x7 factorial arrangement in a completely randomized design. Dried leaves were milled and assayed for vitamins (pyridoxine, riboflavin, ascorbic acid and tocopherol) and provitamins (total carotene and ergocalciferol). Samples were stored in opaque airtight containers after drying and assayed periodically at weeks 0, 3, 6, 9, 12, 15 and 18 of storage. Air dried samples had significantly higher (P